Uniform Lithium Nucleation Guided by Atomically Dispersed Lithiophilic CoNx Sites for Safe Lithium Metal Batteries. Issue 9 (21st November 2018) - Liu, He; Chen, Xiang; Cheng, Xin‐Bing; Li, Bo‐Quan; Zhang, Rui; Wang, Bin; Chen, Xiao; Zhang, Qiang
Abstract: The mossy lithium dendrite growth during repeated lithium plating/stripping induces low Coulombic efficiency, poor lifespan, and safety concerns of working lithium metal batteries. Herein, atomically dispersed CoN x ‐doped graphene is exploited as a host to accommodate dendrite‐free lithium deposits. The coordination between Co and N in the conductive matrix can effectively regulate the local electronic structure, and thereby enhance the adsorption of lithium ions and promote the following nucleation process. Meanwhile, the doped N facilitates high dispersion of Co atoms into graphene through the CoN coordination bond. The strong lithiophilicity provided by N coordinated with Co promises a uniform lithium nucleation behavior, further contributing to the smooth lithium deposition morphology. These characteristics afford a superhigh Coulombic efficiency of 99.2% at 2.0 mA cm −2 (≈400 cycles) and 5.0 mA cm −2 (350 cycles), and 98.2% at 10.0 mA cm −2 (200 cycles) with a capacity of 2.0 mAh cm −2 . LiFePO4 |CoNC–Li full cells deliver a long lifespan of 340 cycles at 1.0 C (240 cycles for routine cells). This offers fresh insights into effectively regulating the lithiophilic chemistry of lithium metal host toward uniform nucleation and growth of lithium deposits in working high‐energy‐density batteries. Abstract : CoNC material is exploited as a host to accommodate dendrite‐free lithium deposits. The synergy of N and Co interactions leads to enhanced lithiophilicity of the CoNC host. Atomically dispersed lithiophilic CoN x sites promise a uniform lithium nucleation and deposition behavior, finally contributing to a remarkable electrochemical performance at a high current density.